Comparative study of obstetric antiphospholipid syndrome (OAPS) and non-criteria obstetric APS (NC-OAPS): report of 1640 cases from the EUROAPS registry. (3rd October 2019) - Alijotas-Reig, Jaume; Esteve-Valverde, Enrique; Ferrer-Oliveras, Raquel; Sáez-Comet, Luis; Lefkou, Elmina; Mekinian, Arsène; Belizna, Cristina; Ruffatti, Amelia; Hoxha, Ariela; Tincani, Angela; Nalli, Cecilia; Marozio, Luca; et al.
Abstract: Objectives: To compare clinical features, laboratory data and fetal-maternal outcomes between 1000 women with obstetric APS (OAPS) and 640 with aPL-related obstetric complications not fulfilling Sydney criteria (non-criteria OAPS, NC-OAPS). Methods: This was a retrospective and prospective multicentre study from the European Registry on Obstetric Antiphospholipid Syndrome. Results: A total of 1650 women with 5251 episodes, 3601 of which were historical and 1650 latest episodes, were included. Altogether, 1000 cases (OAPS group) fulfilled the Sydney classification criteria and 650 (NC-OAPS group) did not. Ten NC-OAPS cases were excluded for presenting thrombosis during follow-up. All cases were classified as category I (triple positivity or double positivity for aPL) or category II (simple positivity). Overall, aPL laboratory categories showed significant differences: 29.20% in OAPS vs 17.96% in NC-OAPS ( P < 0.0001) for category I, and 70.8% in OAPS vs 82% in NC-OAPS ( P < 0.0001) for category II. Significant differences were observed when current obstetric complications were compared ( P < 0.001). However, major differences between groups were not observed in treatment rates, livebirths and thrombotic complications. In the NC-OAPS group, 176/640 (27.5%) did not fulfil Sydney clinical criteria (subgroup A), 175/640 (27.34%) had a low titre and/or non-persistent aPL positivity but did meet the clinical criteria (subgroup B) and 289/640 (45.15%) had a high aPL titre but did not fulfil Sydney clinical criteria (subgroup C). Conclusion: Significant clinical and laboratory differences were found between groups. Fetal-maternal outcomes were similar in both groups when treated. These results suggest that we could improve our clinical practice with better understanding of NC-OAPS patients.